KREDIT USAHA RAKYAT SUPER MIKRO: MENDIDIK MASYARAKAT BERWIRAUSAHA DI MASA PANDEMI COVID-19 - Anton Adi Suryo Kusuma; Wafrotur Rohmah; Maryadi Maryadi (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2022)
AbstractThe purpose of this study is to describe the Super-micro People's Business Credit (KUR) program in educating people to become entrepreneurs during the Covid-19 pandemic in Klunggean village, Sragen regency,  Centra Java, Indonesia. The research used a qualitative method. The research subjects amounted to six people. The data validity technique used source triangulation. The results of the study show that the implementation of the KUR Super microprogram consisted of 5 stages, namely socialization, registration, survey, disbursement of funds, and coaching. In the socialization stage, BRI officers informed the programs and requirements of the KUR Super microprogram to sub-districts and markets, visited the people, and used social media. They could register at the BRI unit office, contact bank officers, or access the website at https://pinjaman.bri.co.id. The survey was conducted when the registrant has completed the initial stage. The bank officers confirmed business information and customers’ plans and proposed various businesses that could be carried out during the pandemic, so that the business feasibility, capital requirements, and payback period could be seen. After feasible business and capital requirements have been calculated and have obtained the Unit Chief’ approval, the process of disbursing funds could be carried out by asking the customers to sign a letter of agreement and they received business capital in the form of savings. In the last stage, they have taken training (coaching) for at least the first 3 months facilitated by BRI officers to determine business progress.Keywords: super micro people business credits, entrepreneurship, Covid-19